Characteristics of Lifelong Learners for Creative Professional Make up Artists - Khawinpat, Phongdej; Pathumcharoenwattana, Worarat; Ueangchokchai, Choosak (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2021)
The purposes of this research were to study characteristics of lifelong learners of creative professional makeup artists. The results of the study were as follows: The characteristics of lifelong learners in creative professional makeup artists were composed of 4 dimensions. 1) Behavioral dimension, consisted of 17 items. It referred to the actions, traits, or behaviors of creative make-up artist, which were mostly influenced by ones’ own attitudes. 2) Attitude dimension, consisted of 20 items. It referred to the positive views and beliefs towards oneself, other people, the environment, including learning. 3) Skill dimension, consisted of 5 items. It referred to personal abilities derived from practice and learning of the lifelong learners until they had expertise, which enhanced their efficacy in lifelong learning, and 4) knowledge dimension, consisted of 3 items. It referred to information or content obtained from experiences or conceptualizing in various aspects holistically. It’s necessary, useful and valuable for living and pursuing success for the lifelong learners. These 4 dimension could be useful for educators to promote lifelong learning characteristics among creative professional makeup artists.